Utilization Of The Millealab Application As A Virtual Reality Media To Support Self-Directed Learning - Muhammad Indra Alkahfi; Mastur Mastur; Agus Hadi Utama (Green Publisher Indonesia, 2024)
Self-directed learning is a process of organizing, finding, and even evaluating information or learning messages without help from others. MilleaLab is a VR-based application that can provide an immersive learning experience to support learners when doing independent learning. The purpose of writing this article is to conduct a literature study related to the utilization of MilleaLab application to support independent learning. The research method used is qualitative literature study. Data collection techniques through literature study of 25 relevant research articles within the last five years. Findings: (1) MilleaLab can be used anytime and anywhere according to one's own learning initiative. (2) MilleaLab can improve the understanding of abstract concepts, learning motivation, and learning outcomes of students, (3) MilleaLab is used as an immersive and interesting VR-based alternative learning media. The results of this study not only describe the MilleaLab application, but also the utilization of VR technology through the MilleaLab application to support immersive and interesting independent learning of students.